An update on the management of refractory cutaneous lupus erythematosus - Verdelli, Alice; Corrà, Alberto; Mariotti, Elena Biancamaria; Aimo, Cristina; Ruffo di Calabria, Valentina; Volpi, Walter; Quintarelli, Lavinia; Caproni, Marzia (Frontiers in Medicine, 2022)
Management of cutaneous lupus erythematosus (CLE) involves a combination of preventive measures, topical and systemic drugs, fairly similar for the different subtypes. Although guidelines exist, to date, no specific drugs have been specifically licensed for CLE. Antimalarials remain the first-line systemic treatment, but many patients do not respond, making refractory lupus a challenge for clinicians. The choice of alternative medication should be based on effectiveness, safety and cost. Most of the available drugs for CLE have been adapted from systemic lupus erythematosus (SLE) treatment but the existing literature is limited to small studies and evidence often lacks. As knowledge of pathogenesis of both CLE and SLE is improving, promising new therapies are emerging. In this review, we discuss the available medications, focusing on the novelties under development for CLE.